Réponses

2014-06-02T16:48:20+02:00
A= 6+(-8)-(-12)-(+9)+2
  = 6 -8 +12 -9 +2
  = -17 +20
  = 3

B= -52-(-41)+(-32)+18-45
  = -52 +41 -32 +18 -45
  = -129 +59
  = -70

C= 87 -105 -155 +201 -104 +32
  = 320 -364
  = -44

D= -10,5 +5,5 -66,5 -88,5 +0,5 -11,5
  =  -177 +6
  = -171
  • Utilisateur Brainly
2014-06-02T19:22:45+02:00
Réponse
A= 6+(-8)-(-12)-(+9)+2
  = 6 -8 +12 -9 +2
  = -17 +20
  = 3
B= -52-(-41)+(-32)+18-45
  = -52 +41 -32 +18 -45
  = -129 +59
  = -70
C= 87 -105 -155 +201 -104 +32
  = 320 -364
  = -44
D= -10,5 +5,5 -66,5 -88,5 +0,5 -11,5
  =  -177 +6
  = -171